Report of Meeting. The Nineteenth Katowice–Debrecen Winter Seminar on Functional Equations and Inequalities Zakopane (Poland), January 30–February 2, 2019 - AMSil, Redakcja (Annales Mathematicae Silesianae, 2019)
Report of Meeting. The Nineteenth Katowice–Debrecen Winter Seminar on Functional Equations and Inequalities Zakopane (Poland), January 30–February 2, 2019.